2022
DOI: 10.1186/s12906-022-03562-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial photobiomodulation add-on therapy to valproic acid for pentylenetetrazole-induced seizures in peripubertal rats

Abstract: Background Convulsive status epilepticus (CSE) prevention is critical for pediatric patients with epilepsy. Immediate intervention before CSE reduce severity. Despite its wide usage as an anticonvulsant, valproic acid (VPA) results in harmful side effects such as dose-dependent hepatotoxicity. Hence, reducing VPA dosage to minimize side effects while maintaining its efficacy is necessary, and transcranial photobiomodulation (tPBM) add-on therapy could facilitate this. We recently demonstrated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Correspondingly, Radwan et al [51] speculated that tPBM mimics benzodiazepine and barbiturates in its blocking effect on GABA B receptors (i.e. tPBM acts as a positive modulator of GABA B receptors [18]).…”
Section: Supporting Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, Radwan et al [51] speculated that tPBM mimics benzodiazepine and barbiturates in its blocking effect on GABA B receptors (i.e. tPBM acts as a positive modulator of GABA B receptors [18]).…”
Section: Supporting Evidencementioning
confidence: 99%
“…Amnesia elicited by etomidate is caused by the modulation of GABA type A (GABA A ) receptors in the hippocampus [52] [53] [54]. The study by Tsai et al [18] study indicated that tPBM can also modulate GABA A receptors by attenuating the noncompetitive antagonism of PTZ toward the GABA A receptor complex in postsynaptic principal cells.…”
Section: Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial photobiomodulation (tPBM) is the application of PBM transcranially and noninvasively. tPBM has been applied to dementia including Alzheimer's disease, 23 traumatic brain injury, 24 stroke, 25 epilepsy, 17,21,26,27 PTSD, 28 anxiety and depression. 29 Corresponding to the two main mechanisms (α-synnuclein aggregation and mitochondrial dysfunction or failure of mitochondrial biogenesis) and a potential therapeutic target (microglial activation) in the pathogenesis of PD, PBM has correlated therapeutic effects against them respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation (PBM) therapy, previously known as low-level laser (light) therapy (LLLT) 10 , is a novel therapy for the treatment of various neurological disorders. Emerging evidence suggests that PBM protects neurons in epilepsy models, including an SE model [11][12][13][14] . In addition, PBM therapy causes hippocampal alterations 15 .…”
mentioning
confidence: 99%